The influence of the Sound scattering layers on the vertical behaviour of two mesopelagic sharks - Saraiva, Bruno Miguel Monteiro (2021)
As apex predators, large sharks sustain the structure and function of marine communities. However, due to the ever-increasing fishing pressure and their slow life-history traits, shark populations have drastically declined in the last decades. Thus, improved knowledge on shark movements is crucial to implement effective management actions to prevent biodiversity loss and the disruption of marine ecosystems. Vertical patterns of apex predators have regularly been associated with foraging behaviours, yet the direct connection with prey’s vertical distribution and availability is often missing. In the open ocean, large aggregations of zooplanktonic and micronektonic organisms produce two unique acoustical signatures known as sound scattering layers (SSLs), believed to be an essential food source for oceanic predators. The present study uses pop-up satellite archival transmitters data of 22 blue (Prionace glauca) and 17 shortfin mako sharks (Isurus oxyrinchus), tracked within the North Atlantic Ocean, to assess the SSLs influence on these species’ diel vertical migrations (DVM) and foraging patterns. The sharks’ vertical patterns followed the SSLs diel migrations, commonly exhibiting surface-oriented behaviour when daytime micronekton concentrations at the shallow scattering layer (SSL) were higher compared to the upper deep scattering layer (DSL). Also, both species seemed to use the SSLs as foraging grounds, yet, while the mako shark appeared to target non-migrant or semi-migrant prey at the DSL, the blue shark generally favoured higher micronekton concentrations. Nevertheless, temperature and oxygen levels limited the extent of the vertical movements and impact the time spent at depth, sometimes preventing the animals from reaching the DSL. Thus, considering the ongoing expansion of the oxygen minimum zones, some predators might lose access to highly energetic prey and subsequently decrease their fitness. The SSLs showed to affect the sharks’ vertical range and time spent at epipelagic waters, revealing a ...